Estimation of STEADI performance using inertial measurement unit - Jasmine Y. Liang; Mingyue Zhang; Nicholas R. Lamoureux; Jeni Lansing; Li-Shan Chou; Gregory J. Welk (Archives of Gerontology and Geriatrics Plus)
Introduction: Falls present a significant public health concern in the United States as a primary cause of unintentional injury-related deaths among older adults. A fall risk assessment toolkit STEADI developed by the CDC has been shown to predict future falls. However, STEADI has issues with accurate evaluations due to the disagreement on cut-off scores in functional assessments and history-taking questionnaires. Wearable sensor technology offers a practical and quantifiable alternative for assessing an individual's movement performance in real-world environments. The use of Inertial Measurement Units (IMUs) offers considerable potential to enhance fall risk screening. Purpose: The primary aim of this study is to test the agreement of STEADI functional assessment performance measured by the IMUs in comparison to human-based measurements. Method: 27 participants (Age: 74.37 ± 7.21) performed STEADI, including the Four-Stage Balance Test (4SBT), Timed Up & Go Test (TUG), 30-second Chair Stand (30sCS) with IMU placed at the fifth lumbar vertebra which is the proxy location of whole-body Center of Mass. By adopting an equivalent test, the STEADI agreement was tested between the human rater and IMU measurements, giving α = 0.05. Result: Between the results from evaluators and IMU, the difference in TUG is -0.23 s, and the difference in 30sCS is 0.37, which is equivalent to within 4 % and 8 % for TUG and 30sCS, respectively. The difference in single-leg stance during the 4SBT is 0.59 s; however, the calculated equivalence zone is larger (22.7 %). Conclusion: This study demonstrates the feasibility of using IMU sensors to enhance fall risk screening protocols based on the STEADI. Future refinement may still need to enable broader application and effective screening practices on a larger scale of the population.